Associations of Educational Attainment, Occupation, and Community Poverty With Hip Osteoarthritis. Issue 6 (30th May 2013) - Cleveland, Rebecca j.; Schwartz, Todd A.; Prizer, Lindsay P.; Randolph, Randy; Schoster, Britta; Renner, Jordan B.; Jordan, Joanne M.; Callahan, Leigh F.
<x xml:space="preserve">Abstract</x> Objective To examine cross‐sectional baseline data from the Johnston County Osteoarthritis Project for the association between individual and community socioeconomic status (SES) measures with hip osteoarthritis (OA) outcomes. Methods We analyzed data on 3, 087 individuals (68% white and 32% African American). Educational attainment and occupation were used as individual measures of SES. Census block group household poverty rate was used as a measure of community SES. Hip OA outcomes included radiographic OA and symptomatic OA in one or both hip joints. Multivariable logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs) for the association of each hip OA outcome with each SES variable separately, and then with all SES measures simultaneously. Associations between hip OA outcomes and SES variables were evaluated for effect modification by race and sex. Results Living in a community of high household poverty rate showed independent associations with hip radiographic OA in one or both hips (OR 1.50, 95% CI 1.18–1.92) and bilateral (both hips) radiographic OA (OR 1.87, 95% CI 1.32–2.66). Similar independent associations were found between low educational attainment among those with symptomatic OA in one or both hips (OR 1.44, 95% CI 1.09–1.91) or bilateral symptomatic OA (OR 1.91, 95% CI 1.08–3.39), after adjusting for all SES measures simultaneously. No significant associations were observed between occupation and hip OA outcomes, nor did race or sex modify the associations. Conclusion Our data provide evidence that hip OA outcomes are associated with both education and community SES measures, associations that remained after adjustment for covariates and all SES measures.